INVENTORY OF FISHING GEAR IN KECAMATAN TUNGKAL ILIR, TANJUNG JABUNG BARAT, JAMBI - Lisna, Lisna; Vincentia, Agnes; Noferdiman, Noferdiman; Amelia, Jasmine Masyitha (Jurusan Perikanan dan Kelautan, 2018)
This research was conducted at Tungkal Ilir, Jambi on May to July 2017. The aims of this study were (1) to determine the types of fishing gear that operates in Tungkal Ilir, (2) fishing area and (3) the dynamics of operating fishing gear in Tungkal Ilir. Data collection was done by interview and observation. The data will be analyzed descriptively using tables and graphs. Based on the results of this research, the fishing gear used in Tungkal Ilir are gill net, trawl, togok, sondong, trap and long line. Gill net is the largest fishing gear used with 15 fishermen. While the least used fishing gear is trap. The dynamics of fishing is strongly influenced by the season and the type of fishing gear used by the fisherman. The fishing area in Tungkal Ilir ranges from 1 mile to 30 miles